Effect of Metabolic Syndrome on Parkinson’s Disease: A Systematic Review (Clinics, 2021)
Evidence shows that metabolic syndrome (MS) is associated with a greater risk of developing Parkinson’s disease (PD) because of the increase in oxidative stress levels along with other factors such as neuroinflammation and mitochondrial dysfunction. However, because some studies have reported that MS is associated with a lower risk of PD, the relationship between MS and PD should be investigated. This study aimed to investigate the effect of MS on PD. Two authors searched five electronic databases, namely, MEDLINE, PubMed, Scopus, PsycINFO, Web of Science, and Science Direct, for relevant articles between September and October 2020. After screening the title and abstract of all articles, 34 articles were selected for full-text review. Finally, 11 articles meeting the eligibility criteria were included in the study. The quality of articles was critically evaluated using the Joanna Briggs Institute. Overall, we evaluated data from 23,586,349 individuals (including healthy individuals, with MS and PD) aged 30 years or more. In cohort studies, the follow-up period varied between 2 and 30 years. MS contributed considerably to the increase in the incidence of PD. In addition, obesity, a component of MS, alone can increase the probability of developing neurodegenerative diseases. However, despite few studies on MS and PD, changes in cognitive function and more rapid progression of PD disease has been documented in patients with MS using methods commonly used in research.